The Initial Listening Skill of the Undergraduate Students of English Education Department - Allvian Susanto (English Education Department - Universitas Nasional Karangturi, 2021)
This research is aimed to investigate the initial listening skill level of the undergraduate Students of English Education Department (EED) in Universitas Nasional Karangturi Semarang 2020/2021. The descriptive research method is applied in this research setting. The participants of the study are the undergraduate Students of EED in Universitas Nasional Karangturi Semarang 2020/2021. The technique of data collection is through administering IELTS listening. The data collected were analyzed descriptively by identifying the correct and incorrect answers in each section of the test. The result of the study shows that the average level of the students’ listening skill is in the B1 level categorized as the independent user based on the CEFR standard. On average, the students are able to understand straightforward factual information about common everyday or job related topics, identify both general messages and specific details, provided that speech clearly articulated in a generally familiar accent. Moreover, they are able to understand the main points of clear standard speech on familiar matters regularly encountered in work, school, leisure etc., including short narratives. Second, at the individual level, there is a big gap of listening skill between the students with highest and the lowest score. There are also several aspects of the undergraduate students listening skill that should get attention when it comes to the listening course design and development. The aspects are understanding and retaining some specific or key information, and recognizing the relationships and connections between facts in the listening text